Desarrollo de un prototipo de derivador basado en gps monitoreado por radio para aplicaciones en oceanografía (dmr v0.1) - Hernández, J. (2009)
Study of coastal currents has been the main goal of this thesis project. This device has been used by researchers of Facultad de Ingeniería Marítima y Ciencias del Mar (FIMCM) - ESPOL to prove that it works properly, and to validate the project. Requirements made by FIMCM researchers to develop DMR system (Derivador Monitoreado por Radio), needed hardware and software and limitations are described. Also, selected electronic components and its individual functioning are detailed. Programming each module and the description of how DMR system works as a whole is depicted too. Design of physical protection of the drifter is also covered here, with structural analysis and assembly of the drifter prototype. Finally, tests made with DMR system by FIMCM researchers at San Pedro de Manglaralto (CENAIM).